Avaliação da participação popular na política do orçamento participativo: um estudo em Fortaleza no período de 2005-2016 - Santos, Cristiane Vieira dos (2019)
This research aims to evaluate popular participation in the Participatory Budgeting (PB) policy in the city of Fortaleza/CE (Brazil) from 2005 to 2016. Three terms of office were analysed: two by Mayor Luizianne Lins, of the Workers’ Party (Partido dos Trabalhadores/PT), and one by Mayor Roberto Cláudio, of the Brazilian Socialist Party (Partido Socialista Brasileiro/PSB). The issue of this research was the evaluation of the participation of civil society in the construction of public policies from the perspective of civil society itself and also from an institutional point of view. For this reason, we interviewed three segments, namely: (1) managers, (2) technicians and (3) civil society about the execution of the PB policy in Grande Bom Jardim (GBJ). The construction of the public policy evaluation paradigm was based on the fourth generation constructivist evaluation, embracing the experience and the trajectory of the policy and using a qualitative and quantitative approach. The comparative method was used to verify whether similarities and divergences occurred in that policy in the context of the respective governments. A bibliographical and documentary study was also made, in addition to the application of the techniques of the Dialectic Hermeneutic Circle (Círculo Hermenêutico-Dialético/CHD) and semi-structured interviews. Data analysis was developed by content analysis and by the use of a software called Iramuteq, which enabled the construction of a statistical base. It was identified that the formulation and execution of the PB in Fortaleza experienced in PT's management were attempts to adopt a new political culture based on principles that prioritized transparency and respect for the active participation of segments of society, trying to satisfy their desires, democratizing relations and decentralizing public policies. In 2013, under Roberto Cláudio's management, the PB policy went through changes in nomenclature and methodology. The results found demonstrated that, on a participation scale (from 1 to 8), both civil society and managements showed different conceptions of participation, oscillating between steps 3 and 6. Consequently, the PB policy did not reach the ideal of selfmanagement – in other words, the last step of the participation scale.